Segmented reporting by diversified companies in South Africa - N. Bhana (South African Journal of Business Management, 1984)
Segmented financial statements provide more useful information on the prospects of a diversified company than the usual consolidated financial statements. Divisional and geographical segmented financial statements improve the investor's predictive ability and make inter-company comparisons possible. As a result of pressure from investors detailed segmented disclosure is becoming a statutory requirement in the more advanced countries. Diversified companies are becoming the norm in South Africa. However, shareholders are not given segmented reports of the different divisions and geographical regions that have differing risk, profitability, and growth. The Companies Act prescribes insufficient segmented reporting by South African companies. Some of the largest and most diversified companies in South Africa are listed on the stock exchange. However, the Johannesburg Stock Exchange (JSE) has not prescribed any segmented disclosure requirements in addition to that required by the Companies Act. The lack of generally accepted accounting practice has also resulted in listed companies providing segmented reports in an arbitrary and inconsistent manner. It is recommended that the segmented disclosure requirements of the Companies Act and the JSE be amended to bring them in line with the more advanced countries. The accountancy profession should give urgent attention to providing a statement on generally accepted accounting practice relating to segmented disclosure.
Keywords: 650